Pre- and post-natal exposure of children to organophosphate flame retardants: A nationwide survey in France. (October 2022) - Chupeau, Z.; Mercier, F.; Rouxel, E.; Le Bot, B.; Chauvet, G.; Siméon, T.; Bonvallot, N.; Zaros, C.; Chevrier, C.; Glorennec, P.
Graphical abstract: Highlights: Pre and post-natal exposures to 15 organophosphate flame retardants was investigated. Exposure were estimated with concentration in hair of mother and child. Exposure is expressed at national level with national mother child cohort. Prevalence of exposure was high for some compounds. Environmental and personal predictors of exposure were identified. Abstract: The use of organophosphate flame retardants (OPFRs) has been on the rise ever since many brominated flame retardants were banned, back in the 2000 s. The objectives of this study are to describe the pre- and post-natal exposure of children to OPFRs, and to explore their possible determinants. A total of 259 children aged 3.5 years and 388 mothers from the French ELFE mother–child cohort were included. Both pre- and post-natal exposure to OPFRs were assessed, using OPFR concentrations in the hair of pregnant women (in 2011) and their 3.5-year-old children (in 2014–2015) for 15 OPFRs, of which 9 were detected in > 20 % hair samples. The highest geometric means for pre-natal exposure were 272 ng/g for tris(1-chloro-2-propyl) phosphate (TCPP), 69.7 ng/g for ng/g for triphenyl phosphate (TPP) and 54.4 ng/g for tris(1, 3-dichloro-2-propyl) phosphate (TDCPP). The highest geometric means for post-natal exposure were 249.6 ng/g for TCPP, 85.3 ng/g for TDCPP and 83.8 ng/g for 2-ethylhexyl diphenyl phosphate (EHDPP). Correlations were found between both pre-natal exposures, and between pre-and post-natal exposures. No correlation was however found between pre-and post-natal exposures for any given OPFR. Pre-natal exposure to the 9 OPFRs was associated with pre-natal exposure to polybrominated diphenyl ethers 209 (BDE209 ), and 47 (BDE47 ). Maternal BMI was associated with pre-natal exposure to OPFRs other than TBEP. Home renovation work prior to birth was also associated with pre-natal exposure to OPFRs, with the exception of EHDPP, tris(2-butoxyethyl) phosphate (TBEP) and triethyl phosphate (TEP). Determinants of post-natal exposure appeared more disparate across OPFRs; although both the type of flooring in children's rooms and pre-natal exposure to polybrominated diphenyl ethers seem to be associated with post-natal exposure. Lastly, higher socioeconomic status appeared to be associated with lower exposure for several (though not all) OPFRs. The high prevalence of exposure to OPFRs suggests the need for studies to assess the health effects of OPFRs exposure, particularly on children.